TLR9 Ligand Induces the Generation of CD20+ Plasmablasts and Plasma Cells from CD27+ Memory B-Cells - Geffroy-Luseau, Alexandrine; Chiron, David; Descamps, Géraldine; Jégo, Gaëtan; Amiot, Martine; Pellat-Deceunynck, Catherine (Frontiers in Immunology, 2011)
Plasma cells have a heterogeneous phenotype in humans. While bone marrow plasma cells are CD20-CD138+, tonsil plasma cells are CD20+CD138+/- and peripheral plasmablasts are CD20-CD138-. In vitro, plasma cells are mainly generated by the activation of CD27+ memory B-cells through transient stimulation of CD40, and their phenotype appears similar to that of bone marrow plasma cells. While CD20 expression is lost at the plasmablastic stage, CD138 expression appears only at the plasma cell stage. Thus, the CD20+CD138+/- phenotype of tonsil plasma cells does not represent an intermediate stage in the differentiation of memory B-cells into plasma cells. Because it has been previously shown that TLR9 activation was more able than CD40 stimulation to induce the differentiation of IgM+ CD27+ B-cells, we wondered whether TLR9 or CD40 stimulation would induce the same phenotype of plasma cells. Thus, we compared the differentiation of CD27+ B-cells isolated from either the tonsils or peripheral blood and stimulated with either CD40L-expressing fibroblasts or a TLR9 ligand, CpG oligodeoxynucleotide (CpG ODN). We observed that CpG ODN mainly induced CD27+ B-cell differentiation into CD20+CD38+CD138- plasmablasts and CD20+CD38+CD138+/- plasma cells, which appear similar to tonsil plasma cells. Removal of CpG ODN during differentiation induced a decrease in the CD20+ plasmablastic population, and, conversely, stimulation of CD40L-induced preplasmablasts with CpG ODN increased the population of CD20+CD38+ plasmablasts. Analysis of Ig secretion showed that CpG ODN induced increased IgM secretion compared to CD40L. Plasma cells from patients with multiple myeloma, the malignant counterpart of bone marrow plasma cells, rarely express CD20. We show that CpG ODN did not induce or increase CD20 in 9 IgG or IgA myeloma cell lines. These data strongly suggest that CpG ODN mainly targets CD27+ IgM+ B-cells.